Plan individual de autocuidados para la prevención del desgaste por empatía en el equipo técnico del Centro de Equidad y Justicia Quitumbe, durante el periodo de abril a julio de 2016. - Bósquez Mantilla, Katherine Tatiana (2017)
This paperwork is a systematization report on the development and execution of a self care plan by members of the technical team of the “Centro de Equidad y Justicia Quitumbe” occurring between April & July of 2016; created with the aim of preventing in them the compassion fatigue, affectation to which they are exposed due to the work they perform and the type of users they serve. This systematization report includes an interpretation of the instruments generated during the whole process, such as workshop field diaries and individual accompaniments, scales and questionnaires applied that allowed to know the scope of the project; an analysis of the objectives for the intervention is also carried out. The interpretation is divided into different stages in which the project was executed: diagnosis, intervention and evaluation. In addition consists of the theoretical support of several authors specialized in the topics of self-care and compassion fatigue. Finally the conclusion and recommendations are described and show how the implementation of the project allowed the technical team to raise awareness of the need to take care of themselves and the constant implementation of self-care strategies customized to their needs and thus the prevention of compassion fatigue